2015
DOI: 10.1088/0031-9155/61/2/712
|View full text |Cite
|
Sign up to set email alerts
|

Variable ultrasound trigger delay for improved magnetic resonance acoustic radiation force imaging

Abstract: Magnetic resonance acoustic radiation force imaging (MR-ARFI) allows the quantification of microscopic displacements induced by ultrasound pulses, which are proportional to the local acoustic intensity. This study describes a new method to acquire MR-ARFI maps, which reduces the measurement noise in the quantification of displacement as well as improving its robustness in the presence of motion. Two MR-ARFI sequences were compared in this study. The first sequence 'variable MSG' involves switching the polarity… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(20 citation statements)
references
References 16 publications
1
19
0
Order By: Relevance
“…sequence with respiratory gating at 3T, the spatial resolution in this study was considered sufficient to monitor temperature and displacement changes during HIFU sonication. Displacement amplitudes found ex vivo on pig muscle ($40 mm) are in agreement with those from Mougenot et al (17). Auboiroux et al (18) reported from in vivo pig liver, a lower displacement (less than 15 mm) during a transcostal sonication, whereby a significant portion of acoustic power was absorbed by the rib cage.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…sequence with respiratory gating at 3T, the spatial resolution in this study was considered sufficient to monitor temperature and displacement changes during HIFU sonication. Displacement amplitudes found ex vivo on pig muscle ($40 mm) are in agreement with those from Mougenot et al (17). Auboiroux et al (18) reported from in vivo pig liver, a lower displacement (less than 15 mm) during a transcostal sonication, whereby a significant portion of acoustic power was absorbed by the rib cage.…”
Section: Discussionsupporting
confidence: 89%
“…Such a method may also be implemented with a single‐shot EPI. Although voxel size reported in Mougenot et al and Auboiroux et al was smaller in the liver using a segmented EPI acquisition sequence with respiratory gating at 3T, the spatial resolution in this study was considered sufficient to monitor temperature and displacement changes during HIFU sonication. Displacement amplitudes found ex vivo on pig muscle (∼40 µm) are in agreement with those from Mougenot et al .…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Multiple acquisition schemes have been proposed for acquiring MR‐ARFI measurements, including spin echo sequences, which are inherently insensitive to temperature change; and gradient recalled echo (GRE) pulse sequences, which are sensitive to temperature changes. Although the majority of ARFI techniques have been demonstrated in phantoms and ex vivo tissues, in vivo studies recently have been published as well. Depending on the application, MR‐ARFI scan time has been reduced using keyhole or parallel imaging techniques when multiple MR radiofrequency (RF) coils are available .…”
Section: Introductionmentioning
confidence: 99%
“…The correlation between changes in tissue mechanical properties and thermal dose has been investigated using both ultrasound (US) and MR imaging . For MRI assessment of tissue mechanical properties, this typically has been accomplished using a standalone MR‐ARFI sequence, but methods for acquiring simultaneous MR‐ARFI and PRF thermometry have been proposed . These combined MR‐ARFI/PRF sequences are valuable because they can improve the safety of using MR‐ARFI for tissue stiffness investigation, focal spot localization, and phase aberration correction by simultaneously measuring temperature rise to ensure no thermal dose is delivered by the ARFI pulses.…”
Section: Introductionmentioning
confidence: 99%